2019
DOI: 10.22227/1997-0935.2019.6.680-689
|View full text |Cite
|
Sign up to set email alerts
|

Application of slag-alkali binders in jet cement grouting for soil consolidation

Abstract: Introduction. The study proves actuality of the problem connected with obtaining efficient slag-alkali binders for usage in soil jet cement grouting. Replacement of usual portland cement for a slag-alkali binder in geotechnical underground construction activities allows solving a problem of waste (slag) utilization and increase economic efficiency of the soil jet cement grouting. In view of cement grouting technology features and possibility of usage cementation mixtures with various engineering characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Conglomerates based on these binders differ significantly from traditional Portland cement conglomerates, and this is due to the phase-mineralogical composition of the synthesized new formations. Investigating soil cements [4,5], still in the 50s of the 20th century,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conglomerates based on these binders differ significantly from traditional Portland cement conglomerates, and this is due to the phase-mineralogical composition of the synthesized new formations. Investigating soil cements [4,5], still in the 50s of the 20th century,…”
Section: Methodsmentioning
confidence: 99%
“…Structural Engineering and Materials he drew attention to the fact that the substances formed during the hardening of soil cement in composition model the minerals of the Earth's crust, in particular zeolites and other minerals which at high temperatures recrystallize into nephelines, jadeites and feldspars, and by the nature of the synthesis process they are similar to the natural processes of mineral and rock formation. Based on the formulated scientific concepts of a number of scientists [4][5][6][7] it was found that the synthesis processes occurring in the Earth's crust are essentially similar to the industrial synthesis processes and the resulting conglomerates have increased durability and corrosion resistance. To obtain 1 ton of Portland cement, it is necessary to consume 179 kg of equivalent fuel and 110 kWh of electricity, and to obtain 1 ton of lime-silica binder -only 79 kg of fuel equivalent and 67 kWh of electricity [8].…”
mentioning
confidence: 99%
“…В настоящее время исследования направлены на получение многокомпонентных вяжущих с низкой долей портландцементного клинкера и бесклинкерных цементов на основе побочных продуктов промышленности [10][11][12]. Продукты гидратации этих вяжущих различаются химическим и минералогическим составом, а также структурой цементного камня на разных уровнях и, соответственно, свойствами [13][14][15].…”
Section: Introductionunclassified